Hepatic perivascular epithelioid cell tumor: a retrospective analysis of 36 cases - Ji, Min; Zhang, Yuchen; Liu, Shuaibing; Zhang, Menghui; Qiao, Bingbing (Frontiers in Oncology, 2024)
Background and aims Hepatic perivascular epithelioid cell tumor (PEComa) is a rare type of mesenchymal neoplasm and lacks systematic reports. The aim was to analyze the features of hepatic PEComa in order to provide our own experience for diagnosis and management from a single center. Methods We retrospectively analyzed clinical data, imaging findings, pathology, treatments and prognosis of 36 patients with hepatic PEComa in the First Affiliated Hospital of Zhengzhou University from January 2016 to September 2023. Results 29 females and 7 males (median age, 47.8 years) were included in this study. The majority (26/36, 72.2%) of patients were diagnosed incidentally with non-specific symptoms. Abnormal enhancement of enlarged blood vessels (27/36,75%) can be observed on CT/MRI and only 7 patients (19.4%) were correctly diagnosed by imaging examinations. The positive immunohistochemical expressions were HMB-45(35/36,97.2%), Melan-A (34/35,97.1%), SMA (23/26,88.5%) and CD34(86.7%,26/30). Treatments include resection (24/36,67.7%), radiofrequency ablation (6/36,16.7%), transcatheter arterial chemoembolization(1/36,2.7%), conservative clinical follow-up(2/36,5.6%), and sirolimus-chemotherapy (3/36,8.3%). During the follow-up period (range, 2–81 months), except for one patient with a single intrahepatic recurrence and 3 malignant patients died in 6 months, the remaining patients had no signs of recurrence and metastasis. Conclusions Hepatic PEComa has no specific clinical features and mainly depends on clinicopathological characteristics for accurate diagnosis. Resection is the best treatment for benign PEComa, but TACE and radiofrequency ablation can also be considered in case of contraindications for surgery.